Typical situations in the system of information support of the investigation of knitting - Khlus, Alexander M. (Journal of the Belarusian State University. Law, 2019)
The article based on the analysis revealed a difference in the understanding of the investigative situation as one of the significant forensic categories. The author’s wording of the concept «typical investigative situation of bribery» is proposed and its types are named. The value of a tactical operation, which contributes to exposing subjects of bribery, is shown. The conclusion is made about the need for proper assessment of investigative situations. This makes it possible to substantiate the choice of a tactical decision, organize and plan joint actions by the investigator and the body carrying out operational investigative activities, put forward versions and optimize the conduct of investigative actions and operational investigative activities. The development of certain investigative situations may entail negative consequences for citizens who accidentally find themselves in the sphere of procedural activity, which implies targeted activation of prosecutorial oversight of the activities of the bodies engaged in operational investigative activities.